53.6k views
1 vote
Jane evaluates x squared minus 3 x + 5 for x = negative 2 below. Step 1: (negative 2) squared minus 3 (negative 2) + 5 Step 2: Equals negative 4 + 6 + 5 Step 3: Equals 7 What, if any, was Jane's mistake?

1 Answer

3 votes

Answer:

Kindly check explanation

Explanation:

Given the question :

Jane evaluates x squared minus 3 x + 5 for x = negative 2 below. Step 1: (negative 2) squared minus 3 (negative 2) + 5 Step 2: Equals negative 4 + 6 + 5 Step 3: Equals 7 What, if any, was Jane's mistake?

Jane's evaluation :

x² - 3x + 5 for x = - 2

Step 1:

(-2)² - 3(-2) + 5

Step 2:

-4 + 6 + 5

Step 3 :

= 7

Jane's mistake was in STEP2,

evaluating (-2)² = 4 and not - 4

Hence, (-2)² - 3(-2) + 5

= 4 + 6 + 5

= 15

User John Mueller
by
5.4k points